Rabies suspected human cases in and around Jimma zone, south west Ethiopia (Asian Journal of Medical and Biological Research, 2023)
Rabies, a viral disease affecting warm-blooded animals, poses a significant public health concern in Ethiopia, particularly concerning human transmission through dogs. To shed light on the status of suspected rabies cases in humans in the Jimma zone and surrounding areas, a retrospective study was conducted at the Jimma Town Health Center from November 2021 to May 2022. The area's rabies status had been unknown since 2012. From 2019 to 2022, a total of 2,223 suspected human rabies cases were recorded at the Health Center, with Jimma town and Xiro Afeta districts of Jimma zone reporting the highest (62%) and lowest (0.3%) numbers, respectively. Of these cases, 96.9% (2,155) resulted from dog bites, with children under 15 years old constituting the majority (52.8%) of victims. Town areas accounted for 66.8% (1,378) of the cases. Significantly variable occurrences were observed in relation to religious category, season, source of exposure, affected body part, and districts within the Jimma zone (P=0.000). The main challenges identified included an increase in stray dog populations, the absence of control centers, lack of awareness about pre-exposure vaccination for owned dogs, a scarcity of rabies vaccine in local veterinary services, and the unavailability of post-exposure prophylaxis at district health centers. Addressing these issues through awareness campaigns for dog owners on pre-exposure vaccination and ensuring the provision of post-exposure prophylaxis to all district health centers is crucial for controlling and preventing rabies in the study area.Asian J. Med. Biol. Res. 2023, 9 (4), 126-133